2013
DOI: 10.14419/ijans.v2i1.521
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation to assess the Knowledge regarding Prevention and Management of Chickenpox in Children among Mothers having Children below 10 years of age residing at selected community area of Allahabad (India)

Abstract: Chickenpox is a worldwide disease and is no respecter race or class. The incidence increases in spring & winter months in the temperate zones. In the tropics, the peak incidence is during winter and early spring. The disease in fact started spreading from February itself. Lack of knowledge among common people on preventing water contamination is helping the virus to spread rapidly. The descriptive study attempts to assess the knowledge regarding prevention and management of chickenpox among mothers of below 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…A similar type of descriptive study conducted in Kathmandu among 200 adolescents showed that nearly half (49.5%) of them had moderate level of knowledge. 6 The findings are consistent with the present study. Although the study sites were different, both the studies have similar results and this could overall reflect the knowledge status of our country.…”
Section: Discussionsupporting
confidence: 93%
“…A similar type of descriptive study conducted in Kathmandu among 200 adolescents showed that nearly half (49.5%) of them had moderate level of knowledge. 6 The findings are consistent with the present study. Although the study sites were different, both the studies have similar results and this could overall reflect the knowledge status of our country.…”
Section: Discussionsupporting
confidence: 93%